Cardiovascular Stress and Work Productivity among Brickfield Workers - Islam, Sinthea; Jishan , Tawfika Rahman; Yasmin, Shoara; Thamima, Ummay; Nazneen, Afsana; Ameen, Muhammad Syeeful; Sattar, Shahria; Abbas, Md Golam (IAHS Medical Journal, 2024)
Background: One of South-East Asia's oldest chaotic, labor-intensive informal sectors is the brickfield industry. Many individuals working in this sector; are illiterate, deprived, and backward. The brickfield workers were exposed to cardiovascular stress while doing different brick manufacturing operations. The aim of the study is to assess cardiovascular stress and work productivity of the 284 brick field workers. Materials and methods: A cross-sectional study was carried of on the 284 workers working in brickfields of Faridpur sadar, Faridpur, Bangladesh from January 2022 to December 2022. The Cardiac Stress Index (CSI) was used for measuring stress and work productivity was measured by semi structured questionnaire. Results: The mean age of the 284 workers was 38.1±9.5 years. The mean average family income was 12,919.0±2,111.0 taka. One out of three workers (35.2%) had above normal CSI. CSI was significantly associated with worker's average monthly family income (p=0.001) and was above normal among the workers who had monthly family income >15,000 takas (61.3%). CSI was also significantly associated with the working station, working hours, resting hours, and duration of working hours by brick carrier in a day (p<0.05). CSI was above normal among the workers who were working as a brick carrier (55.0%), working >6 hours daily (41.1%), taking rest >1 hour (59.3%), and working >6 hours as a brick carrier daily (64.8%). Conclusion: This study might be helpful for brick-field workers to increase their working productivity and also help to reduce the risk of the cardiovascular event during working environments. IAHS Medical Journal Vol 6(1), June 2023; 15-19